Modelagem da distribuição geográfica de espécies de Plebeia (Apidae, Meliponini) frente às mudanças climáticas na região subtropical - Hickel, Cristiano Kern (2015)
The climate change in future scenarios would result changes in the geographical distribution, ecology and behavior of species. In the case of bees, such changes may have more drastic impacts, because these insects are important pollinators in natural and agricultural environments. Based on this, this study analyzed the effect of climate change on the geographic distribution of seven species of Plebeia of ecological and economic importance in the subtropical zone of South America in the current and future scenarios. For that it were identified climate variables that will most likely affect their distribution. The studied species were P. molesta, P. droryana, P. emerina, P. nigriceps, P. saiqui, P. remota and P. wittmanni. The species distribution was modeled using the variables temperature, rainfall and altitude. To describe future climate it were used bioclimatic variables for the year 2070 under the RCP4.5 scenario from Intergovernmental Panel on Climate Change (IPCC). The analysis of data revealed that P. nigriceps and P. saiqui might have the largest reduction in area in the future (> 60%). On the other hand, P. emerina might have a moderate increase in the occurrence area (2.5%), whereas P. wittmanni, a significant increase (55%). Most of the studied species is strongly associated with the Atlantic Forest biome, and P. droryana and P. remota may be even more restricted to this biome. The estimated temperature change for the future scenario could affect the diapause species of Plebeia and the expected increase in rainfall may negatively influence the flight activity. If the changes in the habitat of the species are confirmed, the pollination service of native plants and crops may be affected.